2018
DOI: 10.1155/2018/6949348
|View full text |Cite
|
Sign up to set email alerts
|

Shexiang Baoxin Pills as an Adjuvant Treatment for Chronic Heart Failure: A System Review and Meta‐Analysis

Abstract: Background Shexiang Baoxin pills (SXBXP), as a Traditional Chinese Medicine, are widely used for chronic heart failure in China. It is essential to systematically assess the efficacy and safety of SXBXP as an adjuvant treatment for chronic heart failure. Methods Seven English and Chinese electronic databases (PubMed, Embase, Cochrane Library, CBM, Wanfang, VMIS, and CNKI) were searched from inception to July 2017. The Cochrane Risk of Bias tool was used to evaluate the methodological quality of eligible studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Previous systematic reviews and meta analyses on Qili Qiangxin capsules, Qishen Yiqi dripping pills, Shexiang Baoxin pills, Wenxin granules, and other oral PCMs show good efficacy and safety in the treatment of HF. [ 16 , 23 – 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic reviews and meta analyses on Qili Qiangxin capsules, Qishen Yiqi dripping pills, Shexiang Baoxin pills, Wenxin granules, and other oral PCMs show good efficacy and safety in the treatment of HF. [ 16 , 23 – 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Perform iterative operations based on preset model parameters. [ 16 , 17 ] After the statistical analysis, the convergence needs to be measured by the potential scale reduction factors (PSRE). The closer the PSRE is to 1, the better the convergence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shexiang Baoxin Pill (SBP), a classic patent medicine derived from the TCM formula Suhexiang Pill of Song Dynasty in China, has been extensively used for the prevention and treatment of CVDs, such as unstable angina, myocardial infarction (MI), and heart failure (HF) ( Zhou et al, 2016 ; Dong T. et al, 2018 ). There are seven TCM materials contained in the SBP: Artificial Moschus, Radix Ginseng (Root of Panax ginseng C.A.Mey.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of preclinical studies, SBP has demonstrated therapeutic effects on CVDs via various beneficial mechanisms including regulating angiogenesis and coronary artery dilation, repressing inflammation and oxidation stress, improving lipid metabolism, and protecting vascular endothelium ( Ning et al, 2011 ; Xu et al, 2011 ; Zhang et al, 2017 ; Wei et al, 2018 ). Additionally, in terms of clinical practice, the cardiovascular protective roles of SBP have been proven by several randomized controlled trials and expert consensuses on SBP treatment of CVDs ( Zhou et al, 2016 ; Dong T. et al, 2018 ; Fan et al, 2018 ). In the following sections, we provide an overview of basic experiments and clinical studies on the cardiovascular effects of SBP and the underlying mechanism profiles.…”
Section: Introductionmentioning
confidence: 99%